1994
DOI: 10.1177/088532829400800406
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Investigation of Blood Compatibility of Ti with Oxide Layers of Rutile Structure

Abstract: Structure characteristics of titanium oxide layer on titanium matrix were investigated by Rutherford Backscattering Spectroscopy (RBS), Auger Electron Spectroscopy (AES) and X-ray diffraction. It has been identified that the titanium oxide layers had rutile structure. The blood compatibility of the titanium oxide layers of different thickness was studied by blood clotting time measurement. It was shown that as the thickness of the titanium oxide layers increased, blood compatibility of these layers was obvious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(52 citation statements)
references
References 9 publications
2
50
0
Order By: Relevance
“…Rutile titanium oxide ceramics, TiO 2 and TiO x films prepared by thermal oxidation and ion beamassisted deposition (IBAD) [325][326][327][328][329] generally have blood compatibility better than that of clinically biomaterials, such as LTIC. Hence, titanium oxide is potential a good blood-contacting biomaterial.…”
Section: Oxygen Implantationmentioning
confidence: 99%
“…Rutile titanium oxide ceramics, TiO 2 and TiO x films prepared by thermal oxidation and ion beamassisted deposition (IBAD) [325][326][327][328][329] generally have blood compatibility better than that of clinically biomaterials, such as LTIC. Hence, titanium oxide is potential a good blood-contacting biomaterial.…”
Section: Oxygen Implantationmentioning
confidence: 99%
“…In our study, both HUVEC and EPC were used for coating DHUV with the objective of producing a confluent, functional antithrombotic surface. HUVEC are mature EC that line HUV whereas, EPC can be differentiated into EC and easily be harvested from peripheral blood of patients [38,49]. Generation of an engineered vascular graft usually takes more than 8 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…The change in the optical density of the solution versus time was plotted. Clotting times were estimated for all test materials, including the tubes, non-seeded HUV, cell-seeded HUV and cellseeded HUV with S1P treatment as previously described [38,39].…”
Section: Coagulation and Kinetic Clotting Testsmentioning
confidence: 99%
“…maintenance of tissue structure, wound healing, immune response, metastasis, and tissue integration of biomaterials 18,19) . It was reported that cell spreading could be divided into three stages shown in and transforms to fibrin monomer, it will quickly cross-link to irreversible thrombus 22) . TiO 2 film has higher dielectric constant and is semiconductive, so it can inhibit the electron transfer, prevent fibrinogen from denaturing and decrease thrombus formation 23) .…”
Section: Methodsmentioning
confidence: 99%